Synthesis of Magnetic Catalyst Derived from Oil Palm Empty Fruit Bunch for Esterification of Oleic Acid: An Optimization Study - Krishnan S.G.; Pua F.-L.; Tan E.-S. (Diponegoro University, 2023)
Esterification; Esters; Fruits; Hematite; Magnetism; Molar ratio; Oleic acid; Palm oil; Acid catalyst; Empty fruit bunches; Esterification of oleic acids; Magnetic catalysts; Oil palm; Oil palm empty fruit bunch; Optimisations; Optimization studies; Sources of energy; ]+ catalyst; Biomass